2013
DOI: 10.1111/mmi.12329
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the transcriptional network controlling white‐opaque switching in Candida albicans

Abstract: Summary The human fungal pathogen Candida albicans can switch between two phenotypic cell types, termed “white” and “opaque.” Both cell types are heritable for many generations, and the switch between the two types occurs epigenetically, that is, without a change in the primary DNA sequence of the genome. Previous work identified six key transcriptional regulators important for white-opaque switching: Wor1, Wor2, Wor3, Czf1, Efg1, and Ahr1. In this work, we describe the structure of the transcriptional network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
245
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(254 citation statements)
references
References 56 publications
9
245
0
Order By: Relevance
“…As the number of data sets increases and the complexity of the systems multiply, new programs must weigh the ability of these models to accurately depict transcriptional effects [128][129][130]. Progressively, integration of previously published expression data sets is informing our understanding of C. albicans transcriptional networks to create more robust and dynamic models of regulation [75,125].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%
See 2 more Smart Citations
“…As the number of data sets increases and the complexity of the systems multiply, new programs must weigh the ability of these models to accurately depict transcriptional effects [128][129][130]. Progressively, integration of previously published expression data sets is informing our understanding of C. albicans transcriptional networks to create more robust and dynamic models of regulation [75,125].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%
“…Transcriptional profiles have now been defined under a wide variety of conditions both in vitro and in vivo [99][100][101][102][103]. Profiling of unique phenotypic states, including white, opaque, gray and GUT (gastrointestinally induced transition), has been used to define the transcriptional networks regulating these states, and has revealed that these networks resemble those controlling cell fate in metazoans [34,75,98,104].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%
See 1 more Smart Citation
“…White-opaque switching is controlled through expression of a master regulator, Wor1 (whiteopaque switching regulator 1), which is highly upregulated in opaque cells and is required for both the transition to and maintenance of the opaque cell type [10][11][12][13]. Wor1 can genetically interact with the other five key regulators, forming a network of positive and negative feedback loops to control white-opaque switching [14,15]. Recently, Wor1 is also found to regulate a phenotypic switch that promotes commensalism when passing through the mammalian gut in MTLa/α cell types [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of in vitro and in vivo experiments demonstrated that the WOPR domain of Wor1 binds DNA in a sequence-specific fashion and defined the DNA sequence recognized by it (Fig. 1B) (11,12). Muc1 expressed independent of TEC1 1 (Mit1) from Saccharomyces cerevisiae, a fourth WOPR-domain protein, and Ryp1 from H. capsulatum have since been shown to recognize this same DNA sequence, representing conservation of the WOPR domain-DNA sequence interactions over a period of 600 million to 1.2 billion years (13).…”
mentioning
confidence: 99%